'Cape Town Knows, but She Forgets': Segregation and the Making of a Housing Crisis during the First Half of the 20th Century. Issue 6 (2nd November 2018) - Dooling, Wayne
Abstract : The city of Cape Town experienced a severe housing crisis during the first half of the 20th century, the immediate origins of which were to be found in demographic growth fuelled by natural increase as well as inward migration. The deeper roots of the crisis, however, were in the policy of segregation. This article examines the consequences of the housing shortage for the city's black population and is concerned with segregation as lived experience. The crisis, the scale of which was much greater than previously appreciated, was at its worst during the interwar years. As local state action failed to keep pace with segregatory legislation, the overwhelming majority of the city's population lived under circumstances that could only be described as wretched. For the majority of Cape Town's black population, the segregationist state of the interwar years was simply absent from the housing market.